Determining Economic Growth and Life Expectancy Linkages in Indonesia: A Simultanous Equation Model - Setiawan, Avi Budi; Yusuf, Mochammad; Yudistira, Danu; Nugroho, Agus Dwi (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2023)
Life expectancy become the main indicators of the health parameters in the population and development process. However, there is a relationship between life expectancy and growth which is represented by the inconsistency of previous studies. This study aims to reveal a linkage between life expectancy and economic growth, and analyzing factors that influence both of them. Two-Stage Least Square (2SLS) was used for simultaneous modelling equations to fill the existing literature gaps. Based on the 2SLS estimation relationship, it was found that there is a simultaneous relationship of life expectancy economic growth. Furthermore, it was found economic growth was significantly influenced by the decreasing dependency ratio, unemployment rate, and poverty. Furthermore, life expectancy is positively influenced by health spending and significantly decreases by the increased poverty rate. Therefore, mortality and carbon emissions had insignificant adverse effect. However, poverty and carbon emissions had a negative had insignificant adverse effect. This result suggests the government formulate policies to prioritize larger budget allocations in the education sector as a safety net program, cash transfers, and labor pensions.